The Model of a Polish Diplomat and Its Evolution From the 16th to the 21st century, in the Context of Education, Axiology, Professionalism and Socialization - Urszula Świderska-Włodarczyk (Ignatianum University Press, 2022)
The contemporary model of a Polish diplomat is the result of a long evolution. The first mentions of the topic date back to antiquity and the Middle Ages. It was not until modern times, however, that more interest was vested in this issue. In Western Europe, Niccolo Machiavelli, Torquato Tasso, Abraham de Wicquefort, François de Callierrès, Harold Nicolson, and others have commented on this topic. In Poland, Jakub Przyłuski, Krzysztof Warszewicki, Wawrzyniec Piaseczyński, Stanisław Miński, Tadeusz Morski, Adam Czartoryski - and currently Jerzy M. Nowak, Roman Czyżycki, and Bogdan Grzeloński - have discussed the virtues and vices of diplomats. Their remarks provide a sufficient basis for developing a model of a diplomat and following its evolution over the span of five centuries. To achieve this goal, I utilized my proprietary method of pattern research, analyzing the four components of genealogical, personality, professional, and social conditions. The first is related to one's birth, which can lead to a comprehensive education, good physical condition and inherited wealth. The last one was important in the past, but of no importance now. The second concerns the personal predispositions of a diplomat, in which effectiveness initially took precedence over morality, but morality is now on par with effectiveness. The next set of determinants relates to professionalism, which entails a great responsibility for the position of the state in the international arena and for the fate of one's fellow citizens. Thus, it is more than a profession, as it constitutes a kind of mission and service to one's country. The last component - social conditions - determines the relationships with members of the diplomatic corps, which is especially important today, now that diplomacy has become a team sport. Such a pattern remains difficult to follow, both for past and present generations. However, it is still a desired object of aspiration meant to transform into actual patterns.